Morphological Evaluation of Maxillary Premolar Canals in Iranian Population: A Cone-Beam Computed Tomography Study - Bahar Asheghi; Nariman Momtahan; Safoora Sahebi; Maryam Zangoie Booshehri (Shiraz University of Medical Sciences, 2020)
Statement of the Problem: A thorough knowledge of the morphological and anatomical variations of root canal system can help identify all root canals, adequate instrumentation, and consequently leads to a successful endodontic treatment. The knowledge of root morphology can influence the outcome of root canal therapy. Purpose: The aim of this study was to investigate the morphology of maxillary premolar canals in Iranian population by analyzing cone-beam computed tomography (CBCT) scans. Materials and Method: This cross-sectional retrospective study consisted of CBCT of 280 patients over 16 years of age. The position, number of roots, and root morphology of maxillary premolars were inspected. The root canal configurations of maxillary premolar teeth were also analyzed according to the Vertucci classification. The statistical analyses wee performed using chi-square test. Significance level was set at p < 0.05. Results: In the present study, of 462 maxillary first premolars, 8 (1.73%) teeth had three roots, 222 (48.05%) teeth had two roots, and 232 (50.22%) were single-rooted. In the second maxillary premolar group, of 400 premolars, 2 (0.5%) teeth had three roots, 34 (8.5%) teeth were two-rooted, and 364 (91%) were single-rooted. The most root canal configurations were type IV (71.64%) and type I (63%) in maxillary first and second premolars, respectively. Among females, single rooted premolars were the most prevalent (56.83%), and among males, two-rooted premolars were the most prevalent (57.61%). Conclusion: This study provided information about the root canals of maxillary premolar teeth for Iranian subpopulation leading to more optimal diagnosis and treatment planning for the endodontists. According to the findings, the complexity of root canal system and the number of roots were less common in females compared to males.